A COMPARATIVE EFFECT OF METACOGNITIVE SELF-MONITORING STRATEGIES ON STUDENTSâ READING COMPETENCY BASED ON TEXT TYPES - ELLY PRAPTI ERAWATI, NI LUH PUTU (Jurnal Pendidikan Bahasa, 2012)
ABSTRACT Â  Â  This study attempted to find out a comparative effect of metacognitiveÂ  self-monitoring strategies on studentsâ reading competency based on text types. This study was carried out at the second semester of the second year students of SMA Negeri 2 Denpasar in the academic year of 2011/2012.Â  The independent variable in this research was metacognitive self-monitoring strategies with two levels, namely KWL which stands for Know, Want and Learn and SQ3R strategy which stands for Survey, Question, Read, Recite, and Review, and text types as moderator variable. The dependent variable investigated in this study was reading comprehension. The study was an experimental study with posttest only comparison group design. The total number of population was 10 classes, which consisted of 411 students all together. From the population, two classes, consisting of 64 students, were used as samples. They were divided into two groups; KWL group and SQ3R group by multistage random sampling technique. In this study, the scores of studentsâ reading comprehension were acquired by administering reading comprehension test. The data were analyzed by using two way ANOVA and LSD (least significant difference) test. The result of the analysis showed that: (1) There is no significant difference between the two metacognitive self-monitoring strategies on the studentsâ reading competency. However, the students treated with KWL strategy consistently gained higher scores than the score of student streated with SQ3R. (2) There is no significant difference in reading narrative text competency between students who were taught by using KWL strategy and those who were taught by using SQ3R. (3) There is no significant difference in reading spoof text competency between students who were taught by using KWL strategy and those who were taught by using SQ3R. (4) There is no significant difference in reading hortatory exposition text competency between students who were taught by using KWL strategy and those who were taught by using SQ3R. (5) There was no interaction between metacognitive monitoring strategies and text types. Based on the result of the study, it can be concluded that KWL strategy was better than SQ3R strategy on studentsâ reading comprehension for any text type. Key words: metacognitive self-monitoring strategies, text types and reading comprehension Perbandingan Pengaruh StrategiÂ  Metacognitive Self-Monitoring terhadap Kemampuan Membaca Siswa Berdasarkan Tipe-Tipe Teks. Â  Oleh: Ni Luh Putu Elly Prapti Erawati Â  ABSTRAK Â  Penelitian ini bertujuan untuk menemukan perbandingan pengaruh strategi metacognitive self-monitoring terhadap kemampuan membaca siswa dilihat berdasarkan tipe-tipe teks. Penelitian ini dilaksanakan pada semester gasal, siswa kelas sebelas SMAN 2 Denpasar, tahun ajaran 2011/2012. Variabel bebas pada penelitian ini adalah strategi metacognitive self-monitoring dengan dua level yaitu KWL singkatan dari Know, Want And Learn and SQ3R yakni Survey, Question, Read, Recite, dan Review dan tipe-tipe teks sebagai variabel pembeda. Variabel terikat yang diselidiki dalam penelitian ini adalah kemampuan membaca. Penelitian ini adalah penelitian experimen dengan rancangan posttest only comparison group. Total jumlah populasi 10 kelas yang jumlahnya 411 siswa. Dari populasi tersebut, dua kelas berjumlah 64 siswa terpilih sebagai sampel. Kemudian dengan menggunakan teknik multistage random sampling, mereka dibagi menjadi 2 kelompok; kelompok KWL dan kelompok SQ3R. Pada penelitian ini, skor membaca pemahaman siswa diperoleh dari tes membaca pemahaman. Data kemudian dianalisis dengan menggunakan two way ANOVA dilanjutkan dengan tes LSD (least significant different).Hasil analisis menunjukkan bahwa (1) Tidak terdapat perbedaan yang signifikan diantara kedua strategi metacognitive self-monitoring terhadap kemampuan membaca siswa, tetapi dengan strategi membaca KWL secara konsisten siswa memeroleh nilai rata-rata yang lebih tinggi dibandingkan dengan rata-rata siswa dengan strategi membaca SQ3R. (2) Tidak ada perbedaan yang signifikan dalam kemampuan membaca teks narasi antara siswa yang belajar dengan menggunakan strategi KWL dengan siswa yang belajar dengan strategi SQ3R. (3) Tidak ada perbedaan yang signifikan dalam kemampuan membaca teks spoof antara siswa yang belajar dengan menggunakan strategi KWL dengan siswa yang belajar dengan strategi SQ3R. (4) Tidak ada perbedaan yang signifikan dalam kompetensiÂ  membaca teks hortatory exposition antara siswa yang belajar dengan menggunakan strategi KWL dengan siswa yang belajar dengan strategi SQ3R. (5) tidak ada interaksi antara strategi membaca siswa dengan jenis-jenis teks. Berdasarkan hasil penelitian ini, dapat disimpulkan bahwa strategi KWL lebih baik dibandingkan dengan strategi SQ3R pada kemampuan membaca siswa untuk berbagai jenis teks. Kata Kunci: strategi metacognitive self-monitoring, tipe-tipe teks, kemampuan membaca